Stability and Longitudinal Strength Analysis on Barge 400 Ft During Sea Transportation Decommissioning Jacket - Michael Parulian; Nurmawati; Anggoronadhi Dianiswara (WAVE: Jurnal Ilmiah Teknologi Maritim, 2024)
Transporting a dismantled offshore platform has its challenges in the process. The stability and longitudinal strength of the decommissioning barge used are common problems in this process. Stability analysis will be carried out in intact and damaged conditions while longitudinal strength analysis will be carried out during still water, hogging, and sagging conditions. From the results of the stability analysis that occurred, the initial GM value was obtained in the intact condition of 52.29 m and damage of 47.72 m, 47.69 m, 47.83 m, and 47.81 m. Then, the intact range value that occurred in intact condition was 86° and damage of 82°, 82°, 83.04°, and 82.9°. Next, the ratio area value that occurred in intact condition was 11.22 and damage of 37.24, 43.09, 36.95, and 47.59. Then, from the results of the longitudinal strength analysis, the bending moment value was obtained in still water, hogging, and sagging conditions respectively of 16410 Ton.m, 52740 Ton.m, and 37210 Ton.m and the value of shear forces in still water, hogging, and sagging conditions respectively of 619.092 Ton, 1552.973 Ton, and 1391.362 Ton. The results of stability and strength analysis meet their respective criteria.